Gods and devils: Idolatry and evangelization - Silverblatt, Irene (1982)
Those who study the pre-Hispanic Andean cosmovision today recognize that an uncritical reading of the chroniclers misled many authors who tried to analyze it (Urbano, 1979a). The chroniclers interpreted the societies of the New World based on the beliefs and expectations of their own cultural schemes. This was the case, for example, of the "creator god" they sought in the Andes and whose evidence they thought they found in the mythical heroes viracochas. But a more rigorous analysis of the ethnohistorical sources shows that the existence of a "creator god" does not correspond to the logical and mythical structures of pre-Columbian Andean thought, being rather a consequence of the evangelizing concerns of the first Spaniards and missionaries who arrived in Peru ( Urban, 1974, 1981).